Early Vascular Aging: A New Target for Hypertension Treatment - Papakatsika, Sofia; Stabouli, Stella; Antza, Christina; Kotsis, Vasilios (Current Pharmaceutical Design, 2016)
Vascular aging represents a progressive procedure involving biochemical, enzymatic, and cellular changes of the vascular tree. Early vascular aging (EVA), is defined as the inappropriate for age of vascular damage. Increased for age arterial stiffness is a biomarker that should be considered as a cardiovascular (CV) risk factor that can be manipulated. EVA is a new tool for guidance in everyday clinical praxis for patients at increased CV risk or a positive family history of early onset of cardiovascular events, such as stroke or coronary artery disease. Understanding the mechanisms promoting or protecting from EVA, a process that is in close relationship with CV diseases. The role of hypertension treatment against the development of vascular damage is important and different strategies could have a considerable impact on future vascular health.
Keywords: arterial stiffness